Education 3590. Moral education. No. 17. Moral reasoning approach. - Magsino, Romulo F. (Teacher)
Dr. Magsino discusses moral development and the moral reasoning approach. Includes classroom footage demonstrating the moral reasoning approach in practice. An ETV production.